2009
DOI: 10.1111/j.1442-1984.2009.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional significance of the dark central floret of Daucus carota (Apiaceae) L.; is it an insect mimic?

Abstract: In Daucus carota L. (Apiaceae) the florets comprising the central umbellet of inflorescences are usually pink or dark purple, presenting a marked contrast to the surrounding umbellets, which are generally white. The number of dark florets varies, and some inflorescences have no dark florets. It has been proposed that the dark florets function as an insect mimic, and in so doing serve to attract insects to the flower. In contrast, other authors, Darwin included, suggest that they are functionally redundant. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 20 publications
0
34
1
Order By: Relevance
“…This may be a plausible explanation for the case of dark-colored pattern present in D. guttatus clades 1, 2, 4. Westmoreland and Muntan (1996), and Goulson et al (2009) favored the hypothesis that the dark flowers in umbels of Daucus significantly increase both insect attraction and fruit production. Conversely, Polte and Reinhold (2013) demonstrated that the dark central floret in wild Daucus has no role in pollination, but may play a role in reducing parasite infestation by the gall midge Kiefferia pericarpiicola (Bremi, 1847).…”
Section: ] Arbizu Et Al: Studies Of the Daucus Guttatus Complexmentioning
confidence: 80%
“…This may be a plausible explanation for the case of dark-colored pattern present in D. guttatus clades 1, 2, 4. Westmoreland and Muntan (1996), and Goulson et al (2009) favored the hypothesis that the dark flowers in umbels of Daucus significantly increase both insect attraction and fruit production. Conversely, Polte and Reinhold (2013) demonstrated that the dark central floret in wild Daucus has no role in pollination, but may play a role in reducing parasite infestation by the gall midge Kiefferia pericarpiicola (Bremi, 1847).…”
Section: ] Arbizu Et Al: Studies Of the Daucus Guttatus Complexmentioning
confidence: 80%
“…In about 90 % of individuals, the florets of the central umbellet are pink or purple in color (Lamborn and Ollerton 2000), presenting a marked contrast to the surrounding umbellets, which are generally white. Goulson et al (2009) concluded from their studies that these dark central florets are adaptative and can function as an insect attractant for some insect groups by acting as an insect mimic. The composition of the nectar and/or pollen of D. carota can also play a role in their suitability for different groups of insects.…”
Section: Nectar and Pollen Floral Sugar Composition And Contentmentioning
confidence: 99%
“…In 2007, we grew individuals of Trifolium pratense L. (Fabaceae) and Solanum carolinense L. (Solanaceae) from seed in the greenhouse (see Plate 1). Rudbeckia and Daucus have floral morphologies that are associated with more generalist pollination systems (Waser et al 1996, Goulson et al 2009, and a wide range of insect species visit them in the field, when compared to Solanum and Trifolium (S. Gillespie, personal observation). Solanum was not used in 2008, as plants either failed to germinate or flower that year.…”
Section: Estimating Pollination Servicementioning
confidence: 99%